People's peace : prospects for a human future - Saikia, Yasmin; Haines, Chad (Syracuse studies on peace and conflict resolution., 2019)
""People's Peace: Prospects for a Human Future" is a collection of essays highlighting the everyday and ordinary acts of peace committed by people living in community. The essays span a range of humanities disciplines: history, philosophy, theology, anthropology, cultural studies, and peace studies. Putting these approaches and methods in dialogue with each other produces a theoretical intervention that aims to shift the study of peace away from high organizations and institutions and locate it within people's lives and lived culture. Each essay in this book provides an important instance of people's peace where individuals defy authority or overcome cultural stigmas to assert the value of peaceful relations with others and their own personal dignity. People look for peace, they make peace, and, in doing so, make us aware that common people on their own have always worked and continue to work toward resolution rather than division"--